Hubungan Teman Sebaya dan Media dengan Perilaku Seksual Remaja - Destariyani, Elvi; Yuniarti (AKADEMI KEBIDANAN DHARMA HUSADA KEDIRI, 2024)
The level of sexual behavior in adolescents has increased significantly, especially in several developing countries. Survey results in Bengkulu Province showed that 83.4% of teenagers held hands when dating, 34.2% hugged, 15.6% kissed, and 3.3% touched or stimulated sensitive body parts. This research aims to find out the relationship between peers and the media with adolescent sexual behavior. The design used in the research is cross sectional. Adolescent population at SMPN 20 Bengkulu City. The sample obtained was 87 teenagers taken using stratified random sampling technique. The research data was subjected to statistical tests using the SPSS program. The results of statistical tests showed that there was a relationship between peers (p = 0.000) and information media (p = 0.015) on adolescent sexual behavior at SMPN 20 Bengkulu City. It is hoped that schools can limit teenagers' exposure to risky sexual information media, namely by providing space for teenagers to do physical activities at school and collaborating with health agencies in the area to be able to carry out reproductive health assistance and counseling activities for teenagers so that teenagers can adapt to the process of change. towards adulthood.